“Development” definitions of internally displaced people and the government: A study of the Chenchu tribe in the Nallamala forest of southern India - Jinka Ramamurthy, Malavika; Hoffman, David M. (Frontiers in Conservation Science, 2023)
The Government of India’s twin objectives of protecting the tiger population in the Nallamala forest and providing “development” to the indigenous Chenchu people have resulted in an ongoing process of displacement of the Chenchu people from the forest to the town fringes. While the conservation-displacement nexus has bridged new anthropocentric pathways for development, it has also created deeper crevices in the innate relationships of the Chenchu with the forests and tigers. The research uses a bottom-up approach to present on-the-ground realities of conservation and development policies of the Indian Government and the Chenchu people, particularly, the Chenchu’s development expectations, relationship with the forest and tigers, and displacement views as well as the government’s tiger conservation objectives, development promises, and perspectives on Chenchu development and forest conservation. The paper is a comparative study of the definitions of “development” held by the internally displaced Chenchu people and the Indian government representatives of the Integrated Tribal Development Agency and the Nagarjunasagar Srisailam Tiger Reserve, and the local non-government organizations that collaborate with the Government.